Socio-Cognitive Predictors Of Qol Among Female Adolescent Religious School Students - HINA; Saeed, Dr. Saima; Habib, Dr. Shazia; Batool, Sana; Shaokat, Mohsin Raza; (Corresponding Author), Dr. Saima Saeed (Migration Letters, 2024)
This cross-sectional study was carried out to examine the role of attachment styles, executive functioning, social connectedness, and quality of life among female students of religious schools (called madrassa) in Pakistan. The participants comprised of 12 to 18 years old (Mage = 1.56, SD = .631) girls (N= 200) enrolled in Madrassas in Faisalabad and Sargodha cities. Data were collected using a purposive sampling technique. Self-reported measures including the Urdu versions of Attachment Styles Questionnaire (Bartholomew & Horowitz., 1991), WHOQOL-BREF (WHO, 1998), Social Connectedness Scale (Lee et al., 2001), control measures included Mini-Mental State Examination (MMSE) (Folstein et al., 1975), and Mindfulness Attention Awareness Scale (MAAS), task-based measures included Digits span (WAIS-Ⅳ) (Wechsler, 1997), Stroop Color and Word Test (Stroop, 1935), and Trial Making Test (TMT) A and B forms (Partington & Leiter, 1949). The findings revealed that secure attachment significantly positively correlated with quality of life, and executive functions but not with social connectedness. Secure attachment, cognitive shift, and social connectedness positively predicted QOL. Study indicate strong association between attachment styles and cognitive skills so, improving parenting style play positive role in enhancing executive functioning among religious students. By paying attention on physical and psychological health, cognitive performance of madrassa adolescents might be improved. The findings of the current research might contribute to modify support systems and educational plan. Mental health initiatives can be incorporated to enhance the overall quality of life of female madrasa students.